Comment on "Relict Basin Closure and Crustal Shortening Budgets During Continental Collision: An Example From Caucasus Sediment Provenance" by Cowgill et al. (2016). Issue 3 (25th March 2018) - Vincent, Stephen J.; Saintot, Aline; Mosar, Jon; Okay, Aral I.; Nikishin, Anatoly M.
Plain Language Summary: The southern slope of the Greater Caucasus mountains is the site of a former rift basin. In order to explain shortening deficits, plate deceleration, and the 5 Ma reorganization of the Arabia‐Eurasia collision zone Cowgill et al. (2016) proposed that this basin closed 5 Myrs ago. Within the western Greater Caucasus, at least, careful examination of sedimentological, provenance, and seismic data, however, supports an earlier 35 Ma basin closure age. Basin closure cannot therefore be the driving mechanism for the 5 Ma deceleration of the Arabian plate and reorganization of the Arabia‐Eurasia collision zone. Key Points: Cowgill et al.'s model for Greater Caucasus Basin closure at 5 Ma is not supported by any sedimentological, provenance, or structural data Oligo‐Miocene samples were instead deposited in the southern foreland of the Greater Caucasus following basin closure at 35 Ma Their sparse Jurassic to Eocene provenance data set is insufficient to provide any meaningful insights into the former width of the basin